Can Theories of Empire Explain the American Political Response to the Financial Crisis?. (January 2013) - Tozzo, Brandon
The repercussions of the 2008 financial crisis, which began in the USA, were felt around the world: credit markets froze, consumer demand collapsed, and major banks and industries required government money to avoid bankruptcy. Given the severity of the crisis and the American Government's unprecedented intervention in the economy, the financial crisis presents an ideal case for a critical reassessment of major theories of empire. There are three prominent, yet distinct, views of empire that will be examined in this article. The first is the Empire offered by Michael Hardt and Antonio Negri. The second theory of empire is that of Leo Panitch and Sam Gindin. Finally, there is David Harvey's 'new imperialism'. The purpose of this article is to challenge several limitations in each theory of empire, and to conclude that Harvey's 'new imperialism' provides the greatest insight into the USA's immediate responses to the economic crisis.